(untitled) (Journal of Medical & Health Sciences Review, 2025)
The use of TC (Tetracycline) in the form of long-term aquatic pollutants has led to an urgent need for effective, environmentally friendly treatment technologies. In the present work, copper supported zinc oxide nanoparticles (Cu-ZnO NPs) were prepared and tested as photocatalytic materials for the decomposition of TC in UV light. Comparative study with pristine ZnO was conducted to investigate the effects of copper modification on its photocatalytic activity. At the optimized conditions (pH 5, initial TC concentration of 20 mg/L and 1.0 g/L catalyst dose), a removal efficiency of 95% was attained by using Cu-ZnO, whereas it could only achieve adsorption rate which was less than three and half times higher than that of for ZnO alone. Three variables (pH, initial concentration and catalytic amount) were analyzed through parameter optimization, and it has been found that the degradation was extremely dependent on pH at 5 which provided one best reaction. The kinetic study demonstrated in form of pseudo-first order kinetics with good linear relationship (R2 > 0.99). Temperature-dependent research indicated the rate constant increased from 0.0134 to 0.0250 min⁻¹ with increasing temperature (50-80 °C). Thermodynamic analysis showed that the activation energy was 25.4 kJ/mol, which suggests a moderate energy barrier for practical applications. The positive enthalpy and the large negative entropy of activation supported a well-structured transition state formation in the rate-limiting step. Scavenger studies suggested that hydroxyl radicals were the major reactive species, while holes and superoxide radicals also played a role. The catalyst also exhibited excellent reusability (more than 80% of the activity remained after five recycles).